Geochemical Compositions and Magnetic Susceptibility of Soils from Different Origins: A Case Study in South Lampung, Indonesia - Santoso, Nono Agus; Iqbal, Mochamad; Kadja, Grandprix Thomryes Marth (Geological Agency, 2020)
DOI:10.17014/ijog.7.3.267-272The study of rock weathering into soil is very important in geophysics. The geochemical and magnetic characteristics of soil were investigated in South Lampung using magnetic susceptibility and X-ray Fluorescence (XRF) measurements to identify the rock origin of the soil. The samples consisted of three soil types, those are granite soil, tuff soil in front of ITERA (Institut Teknologi Sumatra, South Lampung), and tuff soil inside ITERA. The tuffs (in front of and inside ITERA) and granite were taken in and around ITERA. The result showed that granite had the highest magnetic susceptibility value, while tuff soil in front of ITERA had the highest FeO content. Each sample can be distinguished by magnetic susceptibility and FeO content to prove that it can be used as a tool to distinguish the rock origin of soil.